ISOLATION, CHARACTERIZATION, AND IDENTIFICATION OF PROTEOLYTIC BACTERIA TO IMPROVE PROTEIN DIGESTIBILITY OF FISH FEED INGREDIENTSISOLATION, CHARACTERIZATION, AND IDENTIFICATION OF PROTEOLYTIC BACTERIA TO IMPROVE PROTEIN DIGESTIBILITY OF FISH FEED INGREDIENTS - Muyasari Mulyasari; Mas Tri Djoko Sunarno; Lusi Herawati Suryaningrum (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2018)
Protease is one of the potential enzymes used to improve the quality of local raw materials as fish feedstuff. The aim of this research was to find high protease activity-bacteria isolates in improving protein digestibility of fish feedstuff. Isolation was conducted on various growth substrates such as water and sediment of hot springs, mangrove sediment, and shrimp head waste. The parameters used in the selection and characterization of potential proteolytic bacteria were qualitative and quantitative tests of proteolytic activity. Microbes that have the highest enzyme activity were then selected and characterized based on their growth curve, production time of protease, and determination of optimum condition (temperature and pH) of protease activity. The result showed that there are only 18 isolates from 44 isolates positively had protease activity (qualitatively). Three isolates with the highest activity (RGL1.1, PL1.1, and PL1.2) qualitatively and quantitatively were then selected to be tested for their pathogenecity on tilapia. The results showed that only RGL1.1 was not pathogenic and therefore, potentially used as a protease producer candidate. The characterization of RGL1.1 isolates showed that the exponential phase of RGL1.1 was thirty-sixth hour in line with the optimum activity of enzyme production. The optimum pH and temperature of RGL1.1 isolate were 6 and 50°C, respectively. RGL1.1 isolate is a Gram-positive rod-shaped bacteria that has 99.53% of resemblance to Bacillus cereus.